2020
DOI: 10.21873/invivo.11944
|View full text |Cite
|
Sign up to set email alerts
|

Re-irradiation With Carbon Ion Radiotherapy for Pelvic Rectal Cancer Recurrences in Patients Previously Irradiated to the Pelvis

Abstract: Background/Aim: Re-irradiation of locally recurrent rectal cancer poses challenges due to the proximity of critical organs, such as the bowel. This study aimed at evaluating the safety and efficacy of re-irradiation with Carbon Ion Radiotherapy (CIRT) in rectal cancer patients with local recurrence. Patients and Methods: Between 2014 and 2018, 14 patients were treated at the National Center of Oncological Hadrontherapy (CNAO Foundation) with CIRT for locally recurrent rectal cancer. Results: All patients concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Moreover, in addition to results for R0 resection rate, our study will provide strong data about tolerance of reirradiation, which remain scarce in a prospective setting. There are, a number of radiotherapy techniques available for use in LRRC, with varying evidence for the use of intensity‐modulated radiotherapy, stereotactic ablative body radiotherapy [23], carbon ion radiotherapy [24,25], intraoperative radiotherapy [26] and proton beam radiotherapy [27]. There is huge potential for future radiotherapy trials in LRRC to build on the robust trial data which GRECCAR 15 will deliver to explore the optimal radiotherapy dose, timing, volumes and radiotherapy techniques with the aim of maximizing radiotherapy treatments and personalizing care in this heterogeneous cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in addition to results for R0 resection rate, our study will provide strong data about tolerance of reirradiation, which remain scarce in a prospective setting. There are, a number of radiotherapy techniques available for use in LRRC, with varying evidence for the use of intensity‐modulated radiotherapy, stereotactic ablative body radiotherapy [23], carbon ion radiotherapy [24,25], intraoperative radiotherapy [26] and proton beam radiotherapy [27]. There is huge potential for future radiotherapy trials in LRRC to build on the robust trial data which GRECCAR 15 will deliver to explore the optimal radiotherapy dose, timing, volumes and radiotherapy techniques with the aim of maximizing radiotherapy treatments and personalizing care in this heterogeneous cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding reirradiation with CIRT for pelvic tumors, Barcellini et al [27] reported that 14 patients with recurrent rectal cancer after radiotherapy underwent CIRT and none of them experienced grade ≥3 toxicities. In our series, 2 patients underwent CIRT for pelvic RAS.…”
Section: Discussionmentioning
confidence: 99%
“…Further, fractionated SBRT might be more advantageous because it allows the re-oxygenation of hypoxic tumour cells and redistribution of resistant tumour cells into more radiosensitive cell cycle phases. 108 Heavy particles, by protons and carbon ions, are emerging as promising treatment RT modality in radioresistant cancers, [109][110][111][112][113][114][115][116] such as pancreatic tumours. [117][118][119][120][121] Proton therapy, thanks to its intrinsic physical selectivity, allows delivering dose to the target with no exit dose in the beam path.…”
Section: Radiotherapymentioning
confidence: 99%